Shared mental models' impact on the onboarding process - Stetzer, Michael W., Jr. (Kansas State University, 2016)
The present study examined onboarding information acquisition and the mediated impact of shared mental model on newcomers' organizational commitment, job satisfaction, and intentions to quit. Onboarding is the initial stage of the socialization process that provides information pertinent to facilitating newcomers' transition into the organization. Previous research stated that a dearth in the socialization literature existed pertaining to intra-individual cognitive mediators. As a result, the present study identified and evaluated the variable, shared mental model, as an underlying mechanism through which information acquisition operated within the onboarding process. The study postulated that newcomers actively evaluated for perceived congruency their own mental models with those espoused by the organization with these perceptions influencing individual organizational commitment, job satisfaction, and intentions to quit. Data were collected via Qualtrics from 305 full-time employees who were experiencing onboarding at the time of study. Participants completed a series of scales relevant to newcomer information seeking behavior, clarity of job role and work processes, and specific organizational outcomes (e.g., organizational commitment, job satisfaction, and intentions to quit) through an online data collection hub. A confirmatory factor analysis supported the factor structures for each of the latent variables (the antecedent, mediator, three socialization outcomes) evaluated in the present study. The proposed mediated socialization process was then examined by way of structural equation modeling. Results showed that shared mental models did mediate the relationships between newcomer employee behaviors and specific socialization outcomes. Furthermore, relationships between the antecedent, newcomer employee behaviors, and two of the socialization consequences, organizational commitment and job satisfaction, appeared to be fully mediated by the presence of shared mental models in the analysis (the intentions to quit relationship was partially mediated). Practical and theoretical implications, in addition to limitations and recommendations of the research are discussed.
Keywords: Shared mental model; Mental model; Organizational socialization; Onboarding